한국 가상자산의 규제 현황 및 그에 따른 과제 - 기존 금융규제체계와의 조화와 규제 불균형의 해소를 중심으로 - 원대성; Won Daesung (지급결제학회지, 2024)
EU는 2018년 3월 “Fintech Action Plan”을 통해 현 EU의 금융규제체계에 대한 가상자산의 적합성 등을 검토하기 시작하였으며, 그 결과 가상자산은 증권법의 적용을 받는 금융상품, 지급결제서비스 관련 법령의 적용을 받는 전자화폐, 그리고 위 2가지 어떤 것에도 해당하지 않는 가상자산으로 나뉠 수 있다는 점을 파악하였으며, 현재 대부분의 가상자산은 금융상품 및 전자화폐에 해당하지 않아 EU 내 금융관련 법령에 따른 소비자 및 투자자 보호 관련 규제, 불공정거래 관련 규제 범위에서 벗어나 있다는 점 등을 파악하여, 이는 MiCA라는 새로운 법 제정의 출발점이 되었다. 2018년부터 이어진 EU의 검토 방법은 우리나라 금융규제체계에 가상자산을 편입함에 있어 판단하여야 할 부분을 명확하게 제시하고 있다는 점에서 현재에도 유효한 연구방법론에 해당하는 바, 한국의 가상자산 관련 규제현황 및 현재 금융규제체계에의 적용여부에 대하여 분석하였다. 한국은 가상자산을 크게 권리 등이 화체된 증권(전자등록주식 등), 지불의 수단(선불전자지급수단 및 전자화폐 등), 그 외의 가상자산 등으로 나누고 있다. 증권의 경우 자본시장법이, 지불의 수단인 경우 전자금융결제법, 그 외의 가상자산의 경우에는 「가상자산 이용자 보호 등에 관한 법률」 (이하 ‘가상자산이용자보호법’이라 한다)이 적용되며, 가상자산 전반에 걸쳐 자금세탁방지를 위해 「특정금융거래정보의 보고 및 이용 등에 관한 법률」이 적용되고 있다. 가상자산이 증권에 해당하는 경우, 가상자산의 발행, 투자자 간의 제2의 시장인 유통, 마지막으로 거래가 완결되는 청산 및 결제, 그리고 증권인 가상자산을 다루는 금융투자업자에 대한 진입규제 등 많은 규제들이 적용된다. 가상자산이 전자지급수단에 해당하는 경우 진입, 발행, 이용자 보호, 지급결제제도 관련 규제, 외국환 업무 관련 규제 등이 적용되나, 전자지급수단으로서 예상하지 못했던 가상자산의 탈중앙화 및 이에 따른 투자자간의 거래 등 가상자산이 가지는 특유의 성질에 대해서는 전자금융거래법 등에서 규제되지 않고 있다. 그 외의 가상자산에 대하여, 가상자산이용자보호법이 적용되나, 가상자산을 이용한 불공정거래에 대한 규정 위주로 구성되어 있을 뿐, 그 외 많은 부분에 대해서는 2차 입법으로 남겨놓았다는 점에서 그 효과는 제한적일 것으로 예상된다. 현재 한국의 가상자산 규제를 살펴보면, 가상자산의 다양한 형태와 성격으로 인하여 가상자산이 증권, 전자지급수단, 또는 그 외의 가상자산 중 어느 것에 속하는지에 대한 법적 불확실성이 크다. 그럼에도 가상자산의 법적 성격을 제시하는 감독당국의 가이드라인이 부족한 상황이며, 시장에서는 최대한 법규를 회피하는 방향으로 자의적 해석이 이루어질 것이 예상된다는 점에서, 입법·행정적으로 법적 불확실성을 해소하여야 한다. 증권과 관련하여 많은 규제가 존재한다는 측면과 간략한 절차 및 저렴한 비용을 통해 금전을 조달할 수 있다는 점에서 중소기업들이 이용하기에 용이하다는 측면 등을 고려하였을 때, 가상자산의 발행인에게는 증권이 아닌 다른 법적 성질을 가진 가상자산을 발행하려는 유인이 발생할 수밖에 없다. 다만, 가상자산이 증권이 아니라고 하여, 투자자 및 자본시장에 대하여 발생하는 위험이 없어진다고 할 수 없다는 점을 고려할 필요가 있다. 그러므로, 투자자 보호, 시장 무결성의 확보, 규제차익의 감소라는 측면에서 가상자산의 규제체계는 자본시장법의 체계를 기본으로 하되, 각 규정에서 부족하거나 공백상태에 있는 부분을 자본시장법을 준용하여 보완하는 방식이 적절하다. 다만, 아직 태동기에 있는 가상자산 산업의 현황을 고려하여, 의무 및 규제강도 등을 고려하여 규제체계를 구성하되, 소비자보호에 핵심적인 업권규제에 대해서는 엄격하게 규제할 필요가 있다. 마지막으로, 분산장부기술 등 새로운 기술을 포함하고, 탈중앙화에 따른 문제점 등을 해결하기 위한 금융관련 법령의 개정이 필요하다. In March 2018, the European Union initiated a review of the suitability of virtual assets within the existing EU financial regulatory framework through the “Fintech Action Plan.” This review identified that virtual assets could be categorized into three types: financial products subject to securities laws, electronic money subject to payment services laws, and other virtual assets that do not fall under the first two categories. The review revealed that most virtual assets do not qualify as financial products or electronic money, thereby remaining outside the scope of consumer and investor protection regulations, as well as unfair trading regulations within EU financial laws. This discovery led to the creation of the MiCA (Markets in Crypto-Assets) regulation. The EU’s method of review, ongoing since 2018, remains a valid research methodology for incorporating virtual assets into South Korea’s financial regulatory framework. Therefore, this study analyzes the current status of virtual asset regulation in South Korea and examines its applicability within the existing financial regulatory framework. In South Korea, virtual assets are broadly classified into securities embodying rights (e.g., electronically registered stocks), means of payment (e.g., prepaid electronic payment means and electronic money), and other virtual assets. Securities are governed by the Financial Investment Services and Capital Markets Act, means of payment are regulated under the Electronic Financial Transactions Act, and other virtual assets are regulated by the Act on the Protection of Users of Virtual Assets. Additionally, anti-money laundering measures apply across all virtual assets under the Act on Reporting and Using Specified Financial Transaction Information. When a virtual asset qualifies as a security, numerous regulations apply, including those governing issuance, secondary market trading among investors, settlement, and clearance of transactions, as well as entry regulations for financial investment businesses handling such securities. If a virtual asset qualifies as an electronic payment means, regulations pertaining to entry, issuance, user protection, payment system, and foreign exchange transactions apply. However, specific characteristics of virtual assets, such as decentralization and investor-to-investor trading, are not covered by the Electronic Financial Transactions Act. For other virtual assets, the Act on the Protection of Users of Virtual Assets applies, but this law primarily addresses unfair trading, leaving many aspects to be covered by future legislation, potentially limiting its effectiveness. The current regulatory landscape for virtual assets in South Korea reveals significant legal uncertainty regarding their classification as securities, electronic payment means, or other types of virtual assets. Despite this, there is a lack of clear guidelines from regulatory authorities, leading to potential arbitrary interpretations aimed at circumventing regulations. Hence, it is necessary to address this legal uncertainty through legislative and administrative measures. Given the extensive regulations associated with securities and the relative ease and lower cost of raising funds, small and medium-sized enterprises may be incentivized to issue virtual assets with legal characteristics other than securities. However, it is crucial to recognize that the risks to investors and capital markets do not disappear simply because a virtual asset is not classified as a security. Therefore, to protect investors, ensure market integrity, and reduce regulatory arbitrage, it is appropriate to base the regulatory framework for virtual assets on the principles of the Financial Investment Services and Capital Markets Act, supplementing gaps or inadequacies by applying analogous provisions from the same act. However, considering the nascent state of the virtual asset industry, the regulatory framework should be structured to balance obligations and regulatory intensity, while strictly regulating industry-specific rules essential for consumer protection. Lastly, it is necessary to amend financial laws to incorporate new technologies, such as distributed ledger technology, and address issues arising from decentralization.